2021
DOI: 10.5194/dach2022-12
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Der Klimawandel in den Alpen: Was erwartet uns in Zukunft?

Abstract: <p>Wir präsentieren eine umfassende Analyse des alpinen Klimawandels im 21. Jahrhundert basierend auf den regionalen Klimasimulationen der EURO-CORDEX Initiative. Klimaänderungssignale verschiedener Temperatur- und Niederschlagsindikatoren sowie der natürlichen Schneedecke bis zum Ende des Jahrhunderts wurden unter expliziter Berücksichtigung der Modellunsicherheiten und für drei Treibhausgas-Emissionsszenarien (RCPs 2.6, 4.5 und 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The climate data presented in this study depict a concerning trend of increasing summer temperatures, temperature humidity index (THI), and heat wave (HW) frequency and intensity, particularly over the last three decades; most notably, we propose a definition of heatwaves that incorporates THI, a widely recognized index for assessing livestock heat stress (Herbut et al, 2018;Wijffels et al, 2021). Our findings are in accordance with the literature about climate changes occurring and foreseen in Europe and Italy (Brunetti et al, 2004;Toreti and Desiato, 2008;Christensen et al, 2015;Twardosz et al, 2021;Kotlarski et al, 2022). The regions most affected by these changes are situated in centralnorthern Italy, including the Po Valley and the Alpine Arch, thus interesting breeds such as Rosset and Brogne sheep, and Lariana and Frisa Valtellinese goats.…”
Section: Discussionsupporting
confidence: 92%
“…The climate data presented in this study depict a concerning trend of increasing summer temperatures, temperature humidity index (THI), and heat wave (HW) frequency and intensity, particularly over the last three decades; most notably, we propose a definition of heatwaves that incorporates THI, a widely recognized index for assessing livestock heat stress (Herbut et al, 2018;Wijffels et al, 2021). Our findings are in accordance with the literature about climate changes occurring and foreseen in Europe and Italy (Brunetti et al, 2004;Toreti and Desiato, 2008;Christensen et al, 2015;Twardosz et al, 2021;Kotlarski et al, 2022). The regions most affected by these changes are situated in centralnorthern Italy, including the Po Valley and the Alpine Arch, thus interesting breeds such as Rosset and Brogne sheep, and Lariana and Frisa Valtellinese goats.…”
Section: Discussionsupporting
confidence: 92%
“…Further expanding the eco-model and safeguarding the practice of alpine pasture farming across international boundaries throughout the Alpine region seems desirable to maintain biodiversity and resilience in fragile mountain landscapes. In the Alps, these are under increasing pressure not just from tourism and forest encroachment but also due to global climate change (Kotlarski et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Climate change is expected to rapidly alter the key processes driving tree and forest dynamics in the Alps (Maroschek et al, 2009). Mountain areas such as the Alps are particularly vulnerable to climate change, where temperatures have been increasing faster than the global average (Leonelli et al, 2011;Pepin et al, 2015) and with a further acceleration observed over the recent decades (Kotlarski et al, 2023). With a rapidly warming climate, these ecosystems will likely experience an acceleration of their dynamics (Albrich et al, 2022;Thom and Seidl, 2022), such as changes in their regeneration, growth, and mortality processes (Allen et al, 2010;Morán-Ordóñez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%